(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Empagliflozin is a first-in-class selective sodium-glucose co-transporter-2 (SGLT2) inhibitor that has revolutionized the management of type 2 diabetes mellitus and cardiovascular disease. Unlike conventional antidiabetic agents, empagliflozin exerts its glucose-lowering effects through an insulin-independent mechanism by inhibiting renal glucose reabsorption, thereby increasing urinary glucose excretion. Beyond glycemic control, empagliflozin has demonstrated remarkable cardiovascular and renal protective effects, fundamentally altering the treatment paradigm for patients with heart failure and chronic kidney disease, irrespective of diabetes status. The landmark EMPA-REG OUTCOME trial established its superiority in reducing cardiovascular mortality and heart failure hospitalizations, findings subsequently confirmed in the EMPEROR-Reduced, EMPEROR-Preserved, and EMPA-KIDNEY trials. This comprehensive review examines the chemistry, pharmacology, clinical trial evidence, safety profile, novel formulation strategies, and future research directions for empagliflozin, with particular emphasis on areas suitable for academic research.